Persistency and permanency of two stages splicing languages via Yusof-Goode approach: two initial strings and two rules - Mudaber, Mohammad Hassan; Yuhani, Yusof; Mohd Sham, Mohamad; Wen, Li Lim (Penerbit Universiti Teknologi Malaysia, 2015)
The notation of representing restriction enzymes in the form of double-triple in order to formulate Yusof-Goode (Y-G) splicing system was mathematically proposed by Yusof in 2012. The aim of introducing Y-G splicing system was to study the process of recombinant deoxyribonucleic acid or DNA strand in a translucent way. In real situation, when the recombination action occurs, the recombinant DNA strands which will arise often contain the patterns of the restriction enzymes. Persistency and permanency are two properties of splicing system, which show whether the recombinant DNA strands will be split by the existence of restrictions enzymes or not if the reaction goes to the second stage. In this research, the persistency and permanency of two stages splicing languages according to the number of cutting sites of initial strings as well as crossing sites and context factors of splicing rules are investigated. Therefore, a Y-G splicing system consisting of two initial strings (with two cutting sites) and two rules is used to present the above properties of two stages DNA splicing languages.